Prevalence of Taurodontism Based on Panoramic Radiography at Saraswati Dental Hospital - I Putu Gede Andyka Yasa; I Dewa Ayu Nuraini Sulistiawati; Haris Nasutianto; Ni Kadek Ari Astuti; Anak Agung Kompyang Martini; Anak Agung Istri Agung Feranasari; I Made Agus Astika; Made Krisna Pramudita Wardana (Interdental Jurnal Kedokteran Gigi (IJKG), 2026)
Introduction: Taurodontism is a dental anomaly characterized by an elongated pulp chamber and apically displaced furcation, usually detected radiographically. Early identification is important because it may affect treatment planning. This study aimed to determine the prevalence of taurodontism on panoramic radiographs at Saraswati Dental Hospital. Materials and Methods: This descriptive cross-sectional study included all panoramic radiographs taken from September 2021 to September 2024. Radiographs with good diagnostic quality, patients aged ≥12 years, and clearly visible molars were included. Crown body length (CB) and root length (R) were measured using Cliniview® based on Shaw’s method to calculate the CB/R ratio and classify taurodontism. Measurements were performed independently by three oral and maxillofacial radiologists. Data were analyzed descriptively. Results and Discussion: Of 3,289 panoramic radiographs, 106 taurodontism cases were identified (3.22%). Most cases occurred in adolescents aged 12–25 years (75.47%) and in the mandible (81.14%). Among 220 affected teeth, mandibular second molars were most frequently involved (64.55%). Hypotaurodontism was the most common subtype (66.37%). Conclusion: Taurodontism prevalence was 3.22%, predominantly affecting adolescents, the mandible, and the hypotaurodontism subtype. Early radiographic detection is important for effective dental management.